On the contribution of global aviation to the CO2 radiative forcing of climate. (15th December 2021) - Boucher, Olivier; Borella, Audran; Gasser, Thomas; Hauglustaine, Didier
Abstract: The aviation sector contributes to anthropogenic climate change through both CO2 and non-CO2 radiative effects. The CO2 effect is considered to be much more certain than the non-CO2 effects, yet there are relatively few studies that quantify it. Building on the scientific literature on burden sharing in the wake of the "Brazilian proposal", we discuss how to best attribute a fraction of the CO2 radiative forcing to the aviation sector. For this we use the OSCAR compact Earth System model to estimate a contribution of aviation to the CO2 concentration of 2.18 ppm in 2018. We further estimate the aviation contribution to the 2018 CO2 radiative forcing to be 34.6, 32.6, 32.2 and 28.8 mW m −2 for the proportional, differential, time-sliced and marginal methods, respectively. The time-sliced method has our preference because it is invariant upon disaggregation or recombination and can differentiate the relative impacts of early and late emissions. It leads to a radiative forcing estimate that is 12% larger than the residual method that is commonly used despite not being additive. This work has implications on the total-to-CO2 RF ratio and the assessment of potential mitigation measures involving a trade-off between the CO2 and non-CO2 radiative effects of aviation.